ANALISIS EFEKTIVITAS SIMPAN PINJAM UNTUK PEREMPUAN (SPP) PROGRAM DANA BERGULIR SERTA DAMPAKNYA TERHADAP TINGKAT PENDAPATAN - Amelya, Tessa; Kartikowati, Sri; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims: (1) to analyze and determine differences in income levels personnel Save Loans for Women (SPP) before and after to exploit credit ; and (2) to determine the effectiveness of Save Loans for Women (SPP) member more level of SPP. The Population is 78 members of SPP at Kamang Hilir which is taken all respondent of the research. This research uses a quantitative descriptive design. Data is collected by questionnaire technique. The analysis technique used is descriptive and inferential statistical analysis is paired sample t-test. The results showed that : (1) there are differences in the level personnel SPP before an after to exploit credit Rp.1.137.179, means that there are differences in income t-count 18.718 > t-table 1.991. (2) effectiveness SPP to the level of income entry criteria are not effective (54,20%). That is , the Save Loans for Women (SPP) Revolving Fund Programs not been effective used in Kamang Hilir.Keywords: Save Loans For Women (SPP) Revolving Fund Programs, Income